A Patient with β-Thalassemia Intermedia Secondary to Homozygosity for a Polyadenylation Signal Mutation (AATAAA > AATAGA) (HBB: C.*112A > G) on the β-Globin Gene. (2nd September 2016) - Lim, Yen-Chian; Tan, Karen M.L.; Chong, Samuel S.; Rajendran, Joseph; Sampath, Venkatasreekanth
Abstract: We describe the clinical presentation and laboratory findings of a Malay man with β-thalassemia intermedia (β-TI), secondary to homozygosity for a polyadenylation (polyA) signal mutation (AATA A A > AATA G A) ( HBB : c.*112A > G) on the β-globin gene, and give a brief review of the literature. This is the first report of a homozygous case of this polyA mutation, and highlights the importance of molecular analysis of the globin genes in the diagnosis of thalassemia.